Faroese wh-nominals - Vangsnes, Øystein A (University of Tromsø, 2009)
This paper presents a survey of Faroese wh-nominals, in particular (i) the hvør N construction, (ii) the hvat fyri (ein) N construction, and (iii) the hvat slag av N.dat construction. The first construction involves a wh-item which is used both pronominally, corresponding to English who and what, and adnominally, corresponding to English which, what (N), and what kind of. The second construction is the Faroese version of the was für/what for construction, including versions with and without an indefinite article and with and without both the preposition (fyri) and the indefinite article (i.e. a “bare what” construction). The last construction involves an overt kind noun which must be followed by the preposition av ‘of’ which in turn assigns dative case to the main/head noun. The survey is based on data collected during the NORMS fieldwork in the Faroe Islands in August 2008, focusing on a number of morphosyntactic issues as well as the semantic distinction between kind and token interpretation. The various findings on Faroese are compared to data on other varieties of Germanic, in particular the North Germanic ones.